ROLE OF MAGNESIUM IN PREVENTING POST-OPERATIVE ATRIAL FIBRILLATION AFTER CORONARY ARTERY BYPASS SURGERY - Bakhsh, Muhammad; Abbas, Safdar; Hussain, Raja Mushtaq; Khan, Safdar Ali; Naqvi, SM Shahab (Journal of Ayub Medical College Abbottabad, 2009)
Objective: To assess the role of 3 days of magnesium infusion after coronary artery bypass graft (CABG) surgery in preventing postoperative atrial fibrillation (AF). Place and Duration of Study: Armed Forces Institute of Cardiology (AFIC) & National Institute of Heart Diseases (NIHD), Rawalpindi, from July 2006 to June 2007. Design: Prospective, randomized, non-blinded. Methods: All patients undergoing isolated, initial CABG surgery, and having sinus rhythm before surgery were alternatively randomized into the study or the control group. The exclusion criteria included: history of AF, implanted pacemaker, myocardial infarction postoperatively, use of left ventricular assist devices and renal failure. The patients in the study group received 10 mmol of magnesium sulphate (2.47 gm) dissolved in 100 ml of saline solution infused intravenously over 4 hours, for 3 days. The end point was development of AF for at least 15 minutes or more, or if an episode of AF had to be treated because of symptoms. Results: A total of 220 patients were included in the study, 110 in each group. The incidence of AF was 9% in patients who received the three days of magnesium infusion. The patients without magnesium had an AF incidence of 23% (p<0.001). The hospital stay was also less in the treated group (p=0.055). Conclusion: A 3-days postoperative infusion of magnesium is safe and effective in reduction of possibly life-threatening AF, in patients undergoing primary coronary artery bypass surgery. Keywords: Coronary artery bypass surgery; Postoperative Atrial fibrillation; Magnesium.